Effect of Oil Temperature on Load Capacity and Friction Power Loss in Point Contact Elasto-hydrodynamic Lubrication - Fatehallah, Hassan S; Hammoudi, Zaid S.; Zidane, Lutfy Y. (Al-Nahrain Journal for Engineering Sciences, 2019)
This study presents a numerical analysis for point contact Elasto-hydrodynamic lubrication EHL. The oils used are (0W-30 and 10W-40) as lubricants. The pressure and film-thickness profiles for point contact EHL are evaluated. The aims of this study are to estimate the effect of oil’s temperature on friction force, coefficient of friction and load carrying capacity. By using FORTRAN program, the Forward-iterative method is used, to solve two dimensional (2D) EHL problem. The viscosity is updating in the solution by using Roeland’s model. After the convergence of pressure is done, the friction force, friction power losses, and friction coefficient are calculated. The temperature used ranges from (-20 to 120 oC). The results showed the film-thickness decreases with the increasing of temperature. Though the maximum pressure is not affected, only the pressure distribution and profile are changed, inlet pressure decreases and the pressure profile tends towards a hertzian (dry contact) one. The friction force and the coefficient of friction decrease with the increasing of temperature.